A GPGPU accelerated descriptor for mobile devices - Hofmann, R.; Seichter, H.; Reitmayr, G. (2012 IEEE International Symposium on Mixed and Augmented Reality, 2012)
We present a modified upright SURF feature descriptor for mobile phone GPUs. Our implementation called uSURF-ES is multiple times faster than a comparable CPU variant on the same device. Our results proof the feasibility of modern mobile graphics accelerators for GPGPU tasks especially for the detection phase in natural feature tracking used in Augmented Reality applications.